Participatory Design of an Electronic Cross-Facility Health Record (ECHR) System for Pediatric Palliative Care: A Think-Aloud Study - Theresa Sophie Busse; Chantal Jux; Sven Kernebeck; Larissa Alice Dreier; Dorothee Meyer; Daniel Zenz; Boris Zernikow; Jan Peter Ehlers (MDPI AG, 2021)
Background: Pediatric palliative care (PPC) patients experience years of multisectoral and professional care. An electronic cross-facility health record (ECHR) system can support the immediate exchange of information among PPC professionals. Based on a needs assessment, a prototype ECHR system was developed. Methods: To evaluate potential users' perspective regarding the system, a qualitative observational study was conducted consisting of a concurrent think-aloud session and a semi-structured qualitative interview. Results: Twenty PPC professionals (nurses, physicians) from specialized outpatient PPC teams, a PPC unit, and medical offices rated the ECHR system as a helpful tool to improve the exchange and collection of information, communication between PPC professionals, and treatment planning. From the user's point of view, the basic logic of the ECHR system should be further adapted to improve the interaction of data remirrored from patient records of outpatient and inpatient care with those entered via the system. The users wished for further functions (text search) and content (information on therapies). Some content, such as the treatment process, needs to be further adapted. Conclusion: The developed ECHR system needs to be more specific in some features by offering all available information; while for other features, be less specific to offer a quick overview. The ability to share information promptly and automatically was seen as a tremendous improvement to the quality of care for PPC patients.